2015
DOI: 10.1590/0104-1169.0338.2585
|View full text |Cite
|
Sign up to set email alerts
|

Programmed home visits by nursing professionals to older adults: prevention or treatment?

Abstract: OBJETIVOS: conocer la repercusión de la visita domiciliaria de los profesionales en enfermería a personas de 65 años o más, pluripatológicas, en morbimortalidad. MÉTODO: estudio retrospectivo caso-control por auditoria de historias clínicas. Muestreo aleatorio. Variables principales morbilidad, mortalidad; descriptivas: visitas de la enfermera, filiación, datos clínicos y socio sanitarios. Análisis por medidas de tendencia central, dispersión, posición, tabulación, frecuencias relativas, absolutas; no paramétr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
1
6
0
3
Order By: Relevance
“…From the results of the medical records analysis, it is also observed that health professionals do not fill out the medical records. The same was observed in the results of other investigations that concluded that, in general, the actual activity is not reflected, there is no uniformity in the records and sometimes there is no connection between the specialized medical care centers 12 . However, the medical record is a fundamental tool to ensure communication between the different members of the multidisciplinary staff 11 .…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…From the results of the medical records analysis, it is also observed that health professionals do not fill out the medical records. The same was observed in the results of other investigations that concluded that, in general, the actual activity is not reflected, there is no uniformity in the records and sometimes there is no connection between the specialized medical care centers 12 . However, the medical record is a fundamental tool to ensure communication between the different members of the multidisciplinary staff 11 .…”
Section: Discussionsupporting
confidence: 78%
“…The fact that a vast majority of the abusers belong to the family nucleus makes it difficult to identify cases of abuse 24 , making these data even more alarming. Since the health professionals are the only ones who, in most cases, have access to the abused elderly person, and nurses are the ones who perform most part of home visits 11 - 12 , it is their responsibility to detect and report cases of elder abuse. Therefore, primary care plays a decisive and fundamental role 2 , 18 , 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can be possible to prevent the fatal consequences of polypharmacy such as event adverse, falls or hospital admissions, through the knowledge of the risk factors for polypharmacy, especially in noninstitutionalised OP. In Spain, community nurses perform the highest number of home visits (Dios‐Guerra et al., ), so they have an important role for preventing polypharmacy and self‐medication, because they provide support with the use of medications (Westerbotn, Fahlström, Fastbom, Agüero‐Torres, & Hillerås, ). The nurses have the opportunity to assist in minimising the use of medications and self‐medications and have also the opportunity to lead initiatives aiming to educate interdisciplinary team members and patients on improved medication management practices (Kim & Parish, ).…”
Section: Relevance To Clinical Practicementioning
confidence: 99%
“…On the other hand, referring to Spain, community nurses are the health professionals that have most direct contact with OP (Dios‐Guerra, Carmona‐Torres, Ruíz‐Gándara, Muñoz‐Alonso, & Rodríguez‐Borrego, ) and who have an important task in the area of educational health. Community nurses must help OP to deal with medications, for preventing the negative consequences of self‐medication and polypharmacy (Dios‐Guerra & Pérula de Torres, ).…”
Section: Introductionmentioning
confidence: 99%